Embryos under the Microscope - JANE MAIENSCHEIN (Harvard University Press, 2013)
Looking at embryos without a microscope does not show much by itself. Human embryos are too tiny to see at all other than as teensy specks in a laboratory dish at a fertility clinic. Frog embryos are large enough to see, but not with much detail: a big egg cell divides into other cells and then gives rise to a tadpole, which swims around for a while then metamorphoses through a pro cess of changing shape into a frog. Chick embryos are inside eggshells. Other species form in similar ways, and without a microscope to magnify the cells, we cannot see much of the intricate detail that is there in any of them.